2011
DOI: 10.3844/jmssp.2011.20.27
|View full text |Cite
|
Sign up to set email alerts
|

Time Series Forecasting by using Seasonal Autoregressive Integrated Moving Average: Subset, Multiplicative or Additive Model

Abstract: Problem statement: Most of Seasonal Autoregressive Integrated Moving Average (SARIMA) models that used for forecasting seasonal time series are multiplicative SARIMA models. These models assume that there is a significant parameter as a result of multiplication between nonseasonal and seasonal parameters without testing by certain statistical test. Moreover, most popular statistical software such as MINITAB and SPSS only has facility to fit a multiplicative model. The aim of this research is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 20 publications
(16 reference statements)
1
24
0
1
Order By: Relevance
“…Comparisons between different Box-Jenkins time series models can be easily found in the literature [28][29][30][31], but there are very few works comparing the results of different parameter estimation methods. ML and LS were compared in [32] to obtain an ARIMA model to predict the gold price.…”
Section: Autoregressive Integrated Moving Average Processesmentioning
confidence: 99%
“…Comparisons between different Box-Jenkins time series models can be easily found in the literature [28][29][30][31], but there are very few works comparing the results of different parameter estimation methods. ML and LS were compared in [32] to obtain an ARIMA model to predict the gold price.…”
Section: Autoregressive Integrated Moving Average Processesmentioning
confidence: 99%
“…At each time stamp, hourly forecasts are made for the next 24 h. Due to daily periodic characteristics of load curves, forecasts are made using a multiplicative seasonal auto-regressive integrated moving average model (ARIMA) [19,20]. With consideration of daily periodicity as well as short-term disturbance, ARIMA (0,1,1) with seasonal moving average part MA (24) are applied, i.e., ARIMA (0,1,1) × (0,1,1) 24 .…”
Section: Optimization In An Online Modementioning
confidence: 99%
“…One of the important time series modeling techniques used in forecasting tourism demand is the SARIMA modeling which is based on the standard Box-Jenkins methodology. Studies that have employed SARIMA modeling in forecasting the tourist arrivals include Chaitip et al [1], Nanthakumar and Ibrahim [2], Saayman and Saayman [3], Suhartono [4] and Padhan [5] among others. Generally, these studies show that the SARIMA model outperforms other competing models in terms of forecasting.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study found positive growth in the number of tourist arrivals to Thailand and SARIMA model is said to be the best model. Similarly, Suhartono [4] proposed a new procedure for modeling the airline data and the number of tourist arrivals to Bali. The SARIMA model consists of subset, multiplicative and additive order and the results indicate the modeling of the airline data yielded a subset SARIMA model as the best model, whereas an additive SARIMA model is the best model for forecasting the number of tourist arrivals to Bali.…”
Section: Literature Reviewmentioning
confidence: 99%